Tumor microtubes convey resistance to surgical lesions and chemotherapy in gliomas - Heuer, Sophie; Osswald, Matthias; Solecki, Gergely; Grosch, Julia Katharina; Jung, Erik; Lemke, Dieter; Ratliff, Miriam; Hänggi, Daniel; Wick, Wolfgang; Winkler, Frank (Neuro-Oncology, 2017)
Background: Primary and adaptive resistance against chemo- and radiotherapy and local recurrence after surgery limit the benefits from these standard treatments in glioma patients. Recently we found that glioma cells can extend ultra-long membrane protrusions, “tumor microtubes” (TMs), for brain invasion, proliferation, and interconnection of single cells to a syncytium that is resistant to radiotherapy. We wondered whether TMs also convey resistance to the other 2 standard treatment modalities. Methods: Patient-derived glioblastoma stemlike cell (GBMSC) lines were implanted under a cranial window in mice. Longitudinal in vivo two-photon laser scanning microscopy was used to follow tumor growth, including the fate of single glioma cells over months. Results: After a cylindrical surgical lesion, GBMSCs increasingly extended TMs toward the lesion area, which contributed to the repopulation of this area over many weeks. In fact, an excessive “healing response” was observed in which tumor cell densities significantly exceeded those of unlesioned brain regions over time. Inhibition of TM formation and function by genetic targeting of growth associated protein-43 robustly suppressed this surgery-induced tumor growth reaction, in contrast to standard postsurgical anti-inflammatory treatment with dexamethasone. After one cycle of temozolomide chemotherapy, intra- and intertumoral heterogeneity of TM formation and interconnection was strongly associated with therapy response: when tumor cells were integrated in TM networks, they were more likely to resist chemotherapy. Conclusion: TMs can contribute to the resistance against standard treatment modalities in gliomas. Specific inhibition of TMs is a promising approach to reduce local recurrence after surgery and lower resistance to chemotherapy.
Gesehen am 28.08.2018